ASSESSMENT THE LIPID PROFILES AND CERTAIN ELECTROLYTE SERUM LEVELS IN PEOPLE WITH TYPE 2 DIABETES MELLITUS - Yassin, Namariq adnan; nagi , Sarah Kadhim; Musa, Maryam Jabbar; Badr, Muhammad Hadi; Mohammed , Zainab Jasim (International Journal Multidisciplinary (IJMI), 2024)
The current study aimed to estimate the levels of lipid profile and some electrolytes in the blood serum of a group of patients with type 2 diabetes mellitus (T2DM). In this study, 100 blood samples were collected and divided into two groups, one consisting of 70 samples from people with type 2 diabetes and the other consisting of 30 samples from healthy people considered a control group. The ages of the people ranged from 25 to 70 years . An estimate of glucose levels and lipid profile concentrations (total cholesterol, triglycerides, high-density lipoproteins for cholesterol, low-density lipoproteins for cholesterol, and very low intensity lipoproteins), and estimating the levels of some electrolytes (magnesium, potassium, and calcium). The results showed a very significant increase (P value < 0.0001) in the levels of glucose, total cholesterol, triglycerides, low-density lipoproteins (LDL), and very low-density lipoproteins (VLDL) in people with type 2 diabetes mellitus when compared with the control group. The results also showed a significant decrease (P value < 0.0001) in the average concentration of high-density lipoproteins (HDL) in people with type 2 diabetes mellitus when compared with the control group. The results also showed a significant decrease (P value < 0.0001) in the levels of potassium and magnesium concentrations, and a significant increase (P value = 0.001) was observed in the levels of calcium concentrations when compared with the control group